BERPACARAN DENGAN SEHAT: TANTANGAN GENERASI MILENIAL DI ERA DISRUPSI - Sarah Silalahi; Segen Pasaribu; Mega Pasaribu; Kristina Tobing; Damayanti Nababan (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2022)
Dating is something that is very close to our daily life. Dating in this millennial era, everyone may also be familiar with the component known as the relationship. Dating relationships are especially important for younger adults. Millennials want positional fashion as an extraordinary courtship. Along with the times and technology, millennial fashion relationships are becoming more and more excessive. It depends on the character of the individual with a view to comparing their courtship relationship with certainty or negatively. The millennial generation is often referred to as a very open technology, likes practicality and dares to take risks. In terms of love life, it is now not much different. In younger people, courtship is seen as a method of gaining recognition. For example, the idea that a person is considered a person if he or she already has a partner, daring to have a relationship is considered manly or having a female friend who is handsome or beautiful is considered an achievement.